Family planning in the Philippines assessment of program implementation - Varela, Amelia P. (1976)
This article assesses the family planning program in the Philippines in terms of the organizational/institutional arrangements and processes for policy formulation and program implementation; mobilization and allocation of financial and human resources; delivery system at the field level; popular support and participation; and research and training needs. The Philippine family planning program suffers from a number of weaknesses, such as: conflicts among goals and interests resulting from multi-agency participation; the influence of heavy inputs of foreign funds on program policies and procedures, strategic emphasis, and control mechanisms; inadequate and frequently delayed financial incentives for medical and paramedical personnel; and deficient delivery system resulting from a combination of managerial and environmental factors. To eliminate or at least minimize these deficiencies, program administrators continuously search for alternative schemes
for effective service delivery and for innovative combinations of program strategies and management techniques.
Keywords: Birth control -- Government policy; Birth control; Population policy; Family planning -- Social aspects